Peran Self Esteem terhadap Burnout Guru - Ai Rosyidah (Universitas Kristen Maranatha, 2024)
Self-esteem is an aspect of personality that has the most important role and a big influence on human behavior and attitudes. Individuals who have high self-esteem will feel like they can do something or feel satisfaction in a situation. On the other hand, individuals who have low self-esteem will feel inferior and feel unable to do something, will always feel inadequate, anxious and will develop feelings of burnout. Work saturation or burnout can affect the quality of work, especially for workers, this work burnout is felt more by workers related to fields that serve humanity, one of which is a teacher. This is similar to research conducted on a sample of teachers at SMPN 52 Bandung, to see the influence of self-esteem on the emergence of burnout in teachers. This research uses quantitative research methods with a correlational design. The sample in this research was 30 respondents. The data collection technique uses a questionnaire distributed to respondents. From the results of the t test, it shows that tcount is 5.340 > ttable 1.697 and the significance value is below 0.05. It can be said that self-esteem significantly plays a role on the emergence of burnout in teachers at SMPN 52 Bandung.